IFN-λ: A New Inducer of Local Immunity against Cancer and Infections - Lasfar, Ahmed; Zloza, Andrew; de la Torre, Andrew; Cohen-Solal, Karine A. (Frontiers in Immunology, 2016)
IFN-λ is the newly established type III IFN with unique immunomodulatory functions. In contrast to the IFN-α/β family and to some extent IFN-γ, IFN-λ is apparently acting in specific areas of the body to activate resident immune cells and induces a local immunity, instrumental in preventing particular infections and also keeping transformed cells under control. Mucosal areas of lung and gastrointestinal tracts are now under scrutiny to elucidate the immune mechanisms triggered by IFN-λ and leading to viral protection. New evidence also indicates the crucial role of IFN-λ in promoting innate immunity in solid cancer models. Based on its unique biological activities among the IFN system, new immunotherapeutic approaches are now emerging for the treatment of cancer, infection, and autoimmune diseases. In the present review, we highlight the recent advances of IFN-λ immunomodulatory functions. We also discuss the perspectives of IFN-λ as a therapeutic agent.